POS0089 A DIAGNOSTIC PERFORMANCE STUDY ON RAMAN SPECTROSCOPY INTEGRATED WITH POLARIZED LIGHT MICROSCOPY FOR THE IDENTIFICATION OF MONOSODIUM URATE IN GOUT - Niessink, T.; Giesen, T.; Comarniceanu, A.; Efde, M.; Janssen, M.; Otto, C.; Jansen, T. (Annals of the rheumatic diseases, 2023)
BackgroundThe diagnosis in gout and other crystallopathies is commonly based on polarized light microscopy (PLM) of synovial fluid aspirates. This technique is flawed, however, due to subjectivity, limited reproducibility, and oversensitivity due to artifacts [1]. There is a need for innovative methods to perform synovial fluid analysis with more objectivity/reproducibility. Raman spectroscopy has been applied for identification of MSU in gout, with different technical approaches [2]. Although results are promising, there are no real diagnostic accuracy measures available for any application of Raman spectroscopy in rheumatology.ObjectivesTo enhance the chemical analytical performance of PLM, we have integrated a Raman spectroscope within a standard polarized light microscope (iRPolM). In this study, we investigated the performance of iRPolM as a next-generation method for synovial fluid analysis in gout.MethodsThis is a prospective study, including 200 samples from a peripheral swollen joint subject for diagnostic analysis. The participants formed a consecutive series. Diagnostic performance was measured against the 2015 ACR/EULAR gout classification criteria set, which includes PLM analysis. Furthermore, we compared the analytical performance of iRPolM to identify MSU crystals with ordinary PLM analysis by an experienced rheumatologist.Results:Table 1.Diagnostic and analytical performance of iRPolM. Values given with 95% confidence intervals.Diagnostic performance of iRPolM against 2015 ACR/EULAR classification criteriaAnalytical performance of iRPolM against PLM by rheumatologistSensitivity77.6% (95% CI 65.8-86.9%)91.2% (95% CI 80.7-97.1%)Specificity97.7% (95% CI 93.5-99.5%),97.6% (95% CI 93.0-99.5%)Positive predictive value94.5% (95% CI 84.9-98.2%)94.6% (95% CI 85.0-98.2%),Negative predictive value89.7% (95% CI 84.7-93.1%),96.0% (95% CI 91.2-98.2%)Accuracy91.0% (95% CI 86.2-94.6%)95.6% (95% CI 91.4-98.2%)Positive likelihood ratio34.4 (95% CI 11.2-106.1)37.4 (95% CI 12.2-114.7)Negative likelihood ratio0.23 (95% CI 0.15-0.36)0.09 (95% CI 0.04 to 0.21)67 patients were classified as gout according to 2015 ACR/EULAR classification criteria. 55 samples were positive for MSU according to PLM analysis. iRPolM identified MSU in 55 patients, 52 of which positive for gout. The inter-rater agreement between PLM and iRPolM was very high (к = 0.90).ConclusionWe demonstrate that Raman spectroscopy integrated with polarized light microscopy has a high diagnostic performance as it comes to identification of MSU in synovial fluid samples. Furthermore, Raman Spectroscopy could provide definitive outcomes in cases where analysists with polarized light microscopy faced uncertainties or lookalikes, for example by identifying birefringent objects as glass slivers, microplastics or other non-MSU crystal types. These results show that Raman spectroscopy is a powerful analytical tool for clinicians, and a potential candidate for replacement or enhancement of PLM in clinical care where higher specificity is needed. Raman spectroscopy gives an excellent specificity on the nature of a birefringent object even with lookalikes, improving the specificity of a difficult microscopical diagnosis.References[1]Bernal, J.A., M. Andrés, S. López-Salguero, et al., Agreement Among Multiple Observers on Crystal Identification by Synovial Fluid Microscopy. Arthritis Care Res (Hoboken), 2022.[2]FitzGerald, J.D., Novel Techniques for Synovial Fluid Crystal Analysis, in Synovial Fluid Analysis and The Evaluation of Patients With Arthritis, B.F. Mandell, Editor. 2022, Springer International Publishing: Cham. p. 133-142.AcknowledgementsWe want to thank ReumaNederland for funding of our research.Disclosure of InterestsTom Niessink: None declared, Tanja Giesen: None declared, Antoaneta Comarniceanu: None declared, Monique Efde: None declared, Matthijs Janssen Shareholder of: Human Crystal Research B.V., Cees Otto Shareholder of: Hybriscan Technologies B.V., Tim Jansen Shareholder of: Human Crystal Research B.V.